2023
DOI: 10.3847/1538-4357/ace051
|View full text |Cite
|
Sign up to set email alerts
|

Nozzle Shocks, Disk Tearing, and Streamers Drive Rapid Accretion in 3D GRMHD Simulations of Warped Thin Disks

Nicholas Kaaz,
Matthew T. P. Liska,
Jonatan Jacquemin-Ide
et al.

Abstract: The angular momentum of gas feeding a black hole (BH) may be misaligned with respect to the BH spin, resulting in a tilted accretion disk. Rotation of the BH drags the surrounding spacetime, manifesting as Lense–Thirring torques that lead to disk precession and warping. We study these processes by simulating a thin (H/r = 0.02), highly tilted (  = 65 ° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…In addition, it was recently demonstrated that the physics driving accretion in luminous black holes (e.g., with L  0.01 L Edd ), which are misaligned with the black hole spin axis, is fundamentally different. Namely, dissipation of orbital energy is driven by nozzle shocks induced by strong warping (Kaaz et al 2023;Liska et al 2023) instead of MRI-driven turbulence (e.g., Balbus & Hawley 1991. These nozzle shocks form perpendicular to the line of nodes, where the disk's midplane intersects the equatorial plane of the black hole and increase the radial speed of the gas by 2-3 orders of magnitude in luminous systems that are substantially misaligned.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was recently demonstrated that the physics driving accretion in luminous black holes (e.g., with L  0.01 L Edd ), which are misaligned with the black hole spin axis, is fundamentally different. Namely, dissipation of orbital energy is driven by nozzle shocks induced by strong warping (Kaaz et al 2023;Liska et al 2023) instead of MRI-driven turbulence (e.g., Balbus & Hawley 1991. These nozzle shocks form perpendicular to the line of nodes, where the disk's midplane intersects the equatorial plane of the black hole and increase the radial speed of the gas by 2-3 orders of magnitude in luminous systems that are substantially misaligned.…”
Section: Discussionmentioning
confidence: 99%
“…In astrophysics, the accretion environment around a BH is highly intricate. As mentioned earlier, when the differential Lense-Thirring torques surpass the viscous torques, the tilted thin accretion disk can be torn into multiple sub-disks [45][46][47][48]. Among these, the angular momentum of the inner accretion disk can quickly align with the BH rotation due to the Bardeen-Petterson effect [40,45,49,50], while the outer accretion disk can maintain its original inclination angle for a more extended period.…”
Section: Images Of Hairy Black Holes Illuminated By Multiple Thin Acc...mentioning
confidence: 92%
“…However, there is a phase lag of 10 − 40 • between the disk and the corona. More interestingly, with the help of GRMHD, Liska et al investigated the structural evolution of very thin (dimensionless scaleheight h/r ≤ 0.03), highly inclined accretion disks and observed that the disk can be torn not only into two independently precessing sub-disks, but even into three sub-disks within certain timescales [45][46][47][48]. This occurs because the differential Lense-Thirring torques overwhelm the viscous torques that maintain the integrity of the accretion disk.…”
Section: Introductionmentioning
confidence: 99%
“…A key piece of the puzzle is angular momentum transport, as angular momentum needs to be removed from the disk for it to accrete into the central BH. Accretion is thought to be driven by three different mechanisms: (a) via turbulent (magnetic and/ or hydrodynamic) small-scale torques, often thought to be due to the magnetorotational instability (MRI; Balbus & Hawley 1991), and usually modeled with an α-parameter viscosity prescription (Shakura & Sunyaev 1973); (b) via large-scale poloidal magnetic fields anchored to the disk (Blandford & Payne 1982;Wardle & Koenigl 1993;Ferreira & Pelletier 1995); or (c) via nonaxisymmetric features such as spiral waves, eccentricity, or warps (e.g., Kaaz et al 2023;Liska et al 2023). In this work, we focus on the first two mechanisms.…”
Section: Introductionmentioning
confidence: 99%